Third and Fourth Heart Sounds: Clinical and Haemodynamic Significance - Mahmood, Manzoor; Hoque, Harisul (University Heart Journal, 2019)
Abstract not available University Heart Journal Vol. 15, No. 2, Jul 2019; 40